2019
DOI: 10.1017/s026646741900021x
|View full text |Cite
|
Sign up to set email alerts
|

Congeneric mutualist ant symbionts (Tetraponera, Pseudomyrmecinae) differ in level of protection of their myrmecophyte hosts (Barteria, Passifloraceae)

Abstract: Barteria fistulosa and B. dewevrei, central African rain-forest trees, provide nesting cavities for Tetraponera aethiops and T. latifrons ants, respectively, which protect them against herbivores. To compare protection efficiency between these two symbioses, for 20 plants of each species in two sites in Gabon we measured the time elapsed before ants reached a focal leaf, for host leaves that were undisturbed, damaged (cut with scissors) or subjected to slight vibration (mimicking such damage), and for damaged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…For instance, defending and non‐defending acacia ants in Mexico are distributed among high‐ and low‐reward swollen‐thorn acacia species (Heil et al., 2009). Similarly, two Tetraponera species (Pseudomyrmicinae) mutualistic with two Barteria (Passifloraceae) species have been reported to vary in the sensitivity and response to leaf damage cues (Kokolo et al., 2019). However, those two examples document differences in ant behavior defending different plant species, which is not the case in our study.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, defending and non‐defending acacia ants in Mexico are distributed among high‐ and low‐reward swollen‐thorn acacia species (Heil et al., 2009). Similarly, two Tetraponera species (Pseudomyrmicinae) mutualistic with two Barteria (Passifloraceae) species have been reported to vary in the sensitivity and response to leaf damage cues (Kokolo et al., 2019). However, those two examples document differences in ant behavior defending different plant species, which is not the case in our study.…”
Section: Discussionmentioning
confidence: 99%
“…At a study site in Sapoba Forest, Nigeria, Janzen (1972) reported that both species had similar biology, but that the colonies occurred in a ratio of about 1:100. More recent work in Gabon has shown that the two species have differing hostplant preferences and protective behavior, with T. latifrons occurring more frequently in Barteria dewevrei, and T. aethiops being preferentially associated with Barteria fistulosa and showing a stronger reaction to leaf disturbance (Kokolo et al 2019). Given differences in morphology of the workers and larvae (Wheeler 1918;Wheeler & Wheeler 1956) it seems probable that there are additional biological differences between the two species yet to be discovered.…”
Section: Tetraponera Rufonigra-groupmentioning
confidence: 99%
“…); Kwale: diani Beach [as "diana Beach"] (Krauss, N. l. h.); Mozambique: Cabo Delgado: 24.5 km 346° from Pemba, 20 m (Fisher, B. l.; et al) In the original description the type locality is stated to be "S. Africa" (Smith 1858) but this is almost certainly an error. Tetraponera aethiops occurs in wet tropical forest from Nigeria to dr Congo and western Uganda, and is an obligate inhabitant of two myrmecophytic species of Barteria (Passifloraceae) (Bequaert 1922; Kokolo et al 2019) that do not occur in South Africa. T. aethiops has also been recorded (Stitz 1910) nesting in live stems of Heinsia myrmoecia (rubiaceae), but davidson & McKey (1993) cast doubt on this report, noting that the internodal swellings of that plant are too small to support a large ant species such as T. aethiops.…”
mentioning
confidence: 99%